Sociocultural-Based Character Education at Riyadlul 'Ulum Integrated High School: Riyadlul Ulum Wadda'wah Islamic Boarding School – Tasikmalaya - Rezza Fauzi Muhammad Fahmi; Rizal Ramdhani (Universitas Terbuka, 2023)
This research is focused on examining sociocultural-based character education through observing the cultural backgrounds of the different students at the Riyadlul ‘Ulum Integrated High School - Tasikmalaya. The research method used is the descriptive qualitative type with the determination of informants using a purposive sampling technique. Research data were obtained from observations, interviews, and FGD (Focus Group Discussion) and analyzed using data analysis techniques from Miles and Huberman. Sociocultural-based character education emphasizes the formation of characters that are in accordance with the social values prevailing in society. This is done by introducing these values from an early age through various activities at school or in the community. In sociocultural-based character education, the formation of individual character is not something that is separate from the social and cultural environment in which the individual is located. Therefore, this approach emphasizes the importance of integrating the formation of individual character with social and cultural values that exist in society. Thus, individuals can have strong character, be rooted in a positive culture and social values, and be able to contribute to improving the quality of social life in society.